2004
DOI: 10.1177/0363546503261719
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception of the Shoulder Joint after Surgical Repair for Instability

Abstract: Five years after surgical repair for shoulder instability, the joint position sense improved significantly, to a level of normal, healthy shoulders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
3
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 25 publications
3
55
3
6
Order By: Relevance
“…They even discuss proprioceptive deWcits of 0.2°-0.8° relative to their clinical relevance and conclude that proprioceptive deWcits as measured with the current methods have only a low to moderate clinically relevant correlation with function. For shoulder proprioception authors like Cuomo et al [5] found proprioception diVerences of 2° after shoulder replacement and adjudged them as clinical relevant also as reported Pötzl et al [16] who found a proprioception change of 4°. In the present study on purpose we used an active and not a passive angle reproduction test to advance clinical relevance.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…They even discuss proprioceptive deWcits of 0.2°-0.8° relative to their clinical relevance and conclude that proprioceptive deWcits as measured with the current methods have only a low to moderate clinically relevant correlation with function. For shoulder proprioception authors like Cuomo et al [5] found proprioception diVerences of 2° after shoulder replacement and adjudged them as clinical relevant also as reported Pötzl et al [16] who found a proprioception change of 4°. In the present study on purpose we used an active and not a passive angle reproduction test to advance clinical relevance.…”
Section: Discussionmentioning
confidence: 84%
“…The AAR has been used to assess shoulder proprioception before, for example, in shoulder instability in which Pötzl et al [16] examined the proprioceptive capabilities of 14 patients with recurrent anterior shoulder instability preoperatively and at least 5 years postoperatively using the AAR test. In their series the joint position sense improved on average about 4° in abduction, Xexion, and rotation.…”
Section: Discussionmentioning
confidence: 99%
“…The AAR has been used to assess proprioception before, for example, in shoulder instability where Pötzl and colleagues examined the proprioceptive capabilities of 14 patients with recurrent anterior shoulder instability preoperatively and for at least five years postoperatively using the AAR test [10]. In their series the joint position sense improved significantly in abduction, flexion, and rotation (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This cycle of events is illustrated by the paradigm of pathophysiology that clinicians and researchers use to identify prospective interventions, such as surgery, rehabilitation, and prevention ( Figure 1). In 2 studies, researchers 12,13 have examined the effects of shoulder surgery on the SMS. However, because of the limitations in the design and methods employed in each study, the precise effects of surgery on upper extremity SMS function are unclear.…”
mentioning
confidence: 99%